Pharmacognostic Studies of the Bark of Kandelia candel (L) Druce: Pharmaceutical Science-Pharmacognosy - Habeebulla M , Muhammed; Velraj, Malarkodi (International Journal of Life Science and Pharma Research, 2022)
Kandelia candel Druce (Rhizophoraceae) is one of the true mangrove species found in South- East Asian mangrove communities, and it is reported that the bark of the plant along with pepper or dried ginger and rose water is found beneficial for the treatment of diabetes. Our aim and objective of the present work was to study pharmacognostic and physio-chemical standards for the bark of the plant Kandelia candel. It includes the macroscopy, microscopy, and powder microscopic characteristics of the bark which provide valuable information for the identification of bark. The barks show greyish to reddishbrown colour, it is slightly curved, and sometimes recurved inner the surface shows slightly yellowish red. The histological section of the bark shows the epidermal layer and mostly it is broken and shows periderm, periderm consists of suberise dead phellem cells, several layers of circular cells found in the cortical region, the interior of the bark shows wide radially oblong aerenchyma tissues, calcium oxalate crystals are very common in the bark which is found as druces and prismatic type crystal forms. Powdered drugs showed the presence of fragments of periderm, cortical parenchyma cells, calcium oxalate crystals, and fibres. Physiochemical constants like ash values, extractive values, foaming, swelling indexes, and fluorescent analysis were performed on the powdered drug which is fairly constant for crude drugs it helps to ascertain the purity of the drug. Preliminary phytochemical screening was performed and it reveals the presence of steroids, phenols, tannins, terpenoids, and flavonoids which may be responsible for the pharmacological effect of the bark of Kandelia candel, the results of the study help in setting the standards for the bark of Kandelia candel which can be useful for the identification and authentication of drugs in future.